Produção de celulases por Talaromyces almestokiae CMIAT 055 com uso de materiais lignocelulósicos como indutores - Faheina Junior, Genilton da Silva (2017)
Cellulases are a complex of enzymes for a complete solubilization of cellulose into sugars, thus playing a primordial role into natural carbon cycle through the hydrolysis of lignocellulosic structures. In addition to its applications in the pharmaceutical industry, cellulases are also used in the textile industry, animal and human diet; in the pulp industry; as well as in the production of ethanol. However, the cost of the enzyme preparation is a major impediment in its commercialization and use in different industrial processes. To mitigate the cost that cellulases add to the bioconversion process, strategies have focused on studies that compose all stages of production of the enzymatic complex, such as selection of hyperproducers microorganisms and replacement of components of culture medium by high added-value lignocellulosic materials. The objective of this thesis was to evaluate the production of cellulases through a microorganism isolated from the Amazonian biome, using pseudostem of the banana tree as inducer of the enzyme in submerged fermentation. Among the strategies carried out to reach the main objective are: selection and use of lignocellulosic materials (cashew bagasse, corn flour, corn ear and banana tree pseustem); study of the initial pH and temperature conditions of the submerged fermentation; optimization of the culture medium components through statistical experimental design; study of pH control in bioreactors; study of the agitation system by comparing impellers with different flow profiles in the liquid medium; and study the stability of the enzyme. The strain CMIAT 055 was statistically out of the others, with FPase activity 17.5% lower than the activity expressed by Trichoderma reesei RUT C30, used as positive control. Molecular techniques identified this sample such as Talaromyces almestokiae and was then submitted to continuous fermentations to obtain the following parameters: initial pH 5.0; culture temperature at 30 ° C; inoculum grown on wheat bran; and cellulase production medium with banana tree pseudostem as an inducer. After checking that large concentrations of plant biomass induced the synthesis of the enzymes, the culture medium was submitted to two experimental designs (Plackett-Burman and DCCR), in which only three components of the culture medium were significant and optimized for the large synthesis of FPase and CMCase. In the bioreactor tests, these parameters were beneficial for higher enzyme activities: maintaining the pH at 5.0; use of the Pitched blade impeller and rotating speed at 300 rpm. Comparing the first test with the use of pseudostem of the banana tree in Erlenmeyer flask, to the last fermentation process in bioreactors, it was observed that the activity of total cellulases increased from 424.7 FPU/L to 2172.8 FPU/L. This fact shows that the strategies adopted in this study are a relevant way to reduce the production cost of the enzyme through the use of lignocellulosic materials.